Electrolyte for solid oxide fuel cell as well as preparation method and application of electrolyte
By using Ce0.8CaxSnySb(0.2-x-y)O3 electrolyte material and doping with elements such as calcium, tin and antimony, various problems existing in SOFC at high temperatures are solved, and the excellent corrosion resistance, long-term stability and high ionic conductivity of the electrolyte are achieved, which improves the performance and application value of SOFC.
Patent Information
- Application Number
- CN202411918555.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-04-18
AI Technical Summary
The existing solid oxide fuel cells (SOFCs) have problems such as changes in electrode microstructure, limited material selection, short battery life, difficult sealing, difficult starting, poor hot and cold cycle performance and high preparation costs at high temperatures, which limit their large-scale commercial applications.
Ce0.8CaxSnySb(0.2-x-y)O3 is used as the electrolyte material for solid oxide fuel cells. By doping elements such as calcium, tin and antimony, the oxygen ion conductivity and low-temperature stability of the electrolyte are improved, and structural stability is maintained at high temperatures.
The excellent corrosion resistance, long-term stability, high ionic conductivity and low temperature stability of electrolytes on CO2 and H2O are achieved, and the performance and application value of SOFC are improved.
Abstract
Description
Technical Field
[0001] The invention relates to an electrolyte for a solid oxide fuel cell and a preparation method and application thereof, belonging to the technical field of batteries. Background Art
[0002] Long-term use of fossil energy will lead to environmental pollution, energy resource shortage and other problems, so it is extremely important to reduce environmental pollution and improve energy conversion efficiency. Fuel cells can directly convert chemical energy into electrical energy. It is an advanced energy conversion technology with significant advantages such as high efficiency, low emissions and low noise. There are many types of fuel cells according to the type of electrolyte material. Among them, the operating temperature of solid oxide fuel cells (SOFC) is usually between 400 and 1000 ° C. The relatively high operating temperature effectively promotes the kinetic reaction of the battery, so SOFC does not require precious metal catalysts. SOFC also has the advantage of great fuel flexibility. Almost all combustible fuels, such as hydrogen, CO, natural gas, coal gas and other hydrocarbons, can be used as fuel. In addition, SOFC has many advantages such as fast electrode reaction rate, high durability, high energy conversion efficiency, use of non-precious metal electrodes, and no threat of carbon monoxide poisoning, which has attracted people's attention and is considered to be one of the most promising green energy conversion technologies and fuel cells with the greatest hope of being widely used.
[0003] A typical SOFC single cell consists of a porous oxide cathode, a dense solid electrolyte and a porous ceramic-metal composite anode. Among them, the solid electrolyte, as a key component of SOFC, plays a very important role. Oxygen ions enter the electrolyte under the action of the potential gradient and oxygen concentration difference and migrate to the anode through the oxygen vacancies in the electrolyte, reacting with hydrocarbons to produce H2O and CO2, thereby completing the entire electrochemical reaction. Therefore, the oxygen vacancy concentration is crucial to the ability of the electrolyte to conduct oxygen ions. SOFC's requirements for solid electrolytes are: the electrolyte must be highly dense to avoid direct mixing of fuel and oxidant; the electrolyte material must have a high ionic conductivity (>10 -2 S cm -1 ) and as small an electronic conductivity as possible, not only to avoid voltage loss and current leakage, but also to facilitate the rapid migration of oxygen ions through oxygen vacancies; the electrolyte material needs to have good thermal expansion matching with the contact electrode elements, as well as good structural stability and chemical stability to avoid problems such as battery cracking, falling off and poor contact. In addition, in order to improve the low-temperature performance of the battery, the electrolyte is preferably very thin to minimize the internal resistance of the battery during the electrochemical reaction.
[0004] However, the high operating temperature of SOFC limits its large-scale commercial application. At high temperatures (>1000℃), SOFC will cause a series of problems, such as changes in electrode microstructure (due to side reactions at the electrode / electrolyte interface), limited selection of electrolyte and electrode materials, short battery life, difficult battery sealing, difficult startup, poor hot and cold cycle performance, and high battery preparation costs. In order to develop low-cost SOFC, two approaches can be taken: first, develop new materials with sufficiently high ionic conductivity, high performance and high output power at medium and low temperatures (400-700℃); second, use thin film technology to reduce the thickness of the electrolyte, thereby reducing the ohmic resistance of the electrolyte, so that materials that were previously unsuitable for use at medium and low temperatures can be used. At present, reducing the operating temperature of SOFC and developing low-cost SOFC preparation technology have become the main research directions.
[0005] The electrolyte materials for medium and low temperature SOFCs need to meet a series of necessary conditions: (1) In order to minimize the ohmic resistance of the electrolyte film, the selected electrolyte material should have a high oxygen ion or proton conductivity at the operating temperature. Generally, the ion conductivity should not be less than 10 -2 S / cm; (2) In order to ensure that the fuel cell achieves high energy conversion efficiency, the electronic conductivity of the solid electrolyte material should be as small as possible to be negligible; (3) In order for the electrolyte film to effectively separate the anode fuel and the cathode oxidant, it must be completely dense, and its density is generally required to reach more than 95% of the theoretical density of the bulk material; (4) In the range from room temperature to operating temperature, the electrolyte material should maintain long-term chemical, physical and microstructural stability under strong reducing and strong oxidizing atmospheres; (5) At the battery operating temperature or even higher preparation temperature, the electrolyte material should have good chemical compatibility with the adjacent anode, cathode and sealing materials, and no interface diffusion and chemical reaction will occur; (6) From room temperature to operating temperature or even preparation temperature, the electrolyte material should have a similar thermal expansion coefficient to other battery components to avoid interface bending, cracking or shedding; (7) The electrolyte film should have high mechanical strength, toughness and thermal shock resistance, as well as low cost and simple forming process. Summary of the invention
[0006] In view of this, the purpose of the present invention is to provide an electrolyte for a solid oxide fuel cell, a preparation method and an application thereof. The technical problem to be solved is how to provide an electrolyte for a solid oxide fuel cell that has good resistance to CO2 and H2O corrosion, good long-term stability, high ionic conductivity and low-temperature stability.
[0007] The purpose of the present invention and the technical problems to be solved are achieved by adopting the following technical measures. The present invention proposes a solid oxide fuel cell electrolyte, whose chemical formula is Ce 0.8 Ca x Sn y Sb (0.2-x-y) O3, wherein x is 0.01-0.1 and y is 0.1-0.15.
[0008] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.
[0009] Preferably, the solid oxide fuel cell electrolyte described above, wherein the solid oxide fuel cell electrolyte comprises, by mole percentage:
[0010] Cerium oxide 80 mol%;
[0011] Doping elements 20mo1%.
[0012] Preferably, in the aforementioned solid oxide fuel cell electrolyte, the doping elements include calcium, tin and antimony.
[0013] Preferably, the aforementioned solid oxide fuel cell electrolyte further comprises 5-10 wt % of an additive.
[0014] Preferably, in the aforementioned solid oxide fuel cell electrolyte, the additive is a compatibility enhancer.
[0015] Preferably, in the aforementioned solid oxide fuel cell electrolyte, the compatibility enhancer is calcium zirconate.
[0016] Preferably, the aforementioned solid oxide fuel cell electrolyte, wherein the oxygen ion conductivity of the solid oxide fuel cell electrolyte at 400°C is ≥0.1S / cm; after high temperature cycle testing, the solid oxide fuel cell electrolyte maintains good structural stability at 800°C without obvious phase change or cracks; in an environment containing H2O and CO2, the solid oxide fuel cell electrolyte exhibits excellent anti-pollution properties, and the oxygen ion conductivity is ≥0.07S / cm.
[0017] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a method for preparing an electrolyte for a solid oxide fuel cell, comprising the following steps:
[0018] Step 1: mixing cerium oxide, doping elements and additives in proportion to obtain mixed powder;
[0019] Step 2: sintering the mixed powder obtained in step 1 at 1100-1300° C. for 5-7 hours to obtain a crude electrolyte;
[0020] Step 3: annealing the crude electrolyte obtained in step 2 at 500-550° C. for 1-3 hours to obtain the electrolyte for solid oxide fuel cells.
[0021] The purpose of the present invention and the technical problem to be solved are achieved by adopting the following technical solutions. The present invention proposes a method for preparing an electrolyte for a solid oxide fuel cell, comprising the following steps:
[0022] Step S1: mixing cerium oxide, doping elements and additives in proportion to obtain a mixed powder;
[0023] Step S2: adding 0.1-5wt% of an adhesive and a solvent to the mixed powder obtained in step S1, and stirring evenly to obtain a mixed slurry; forming the obtained mixed slurry into a sheet film with a thickness of less than 50 μm, and cutting the sheet film;
[0024] Step S3: sintering the film obtained in step S2 at 1100-1300° C. for 4-6 hours to obtain the electrolyte for the solid oxide fuel cell.
[0025] The purpose of the present invention and the technical problems to be solved can be further achieved by adopting the following technical measures.
[0026] Preferably, in the aforementioned method for preparing an electrolyte for a solid oxide fuel cell, in step S2, the solvent is pure water or anhydrous ethanol.
[0027] The purpose of the present invention and the technical problems solved therein can also be achieved by adopting the following technical measures: A fuel cell proposed by the present invention comprises an electrolyte, wherein the electrolyte is the electrolyte for solid oxide fuel cells mentioned above.
[0028] Compared with the prior art, the solid oxide fuel cell electrolyte and its preparation method and application described in the present invention have the following beneficial effects:
[0029] The electrolyte for solid oxide fuel cells of the present invention has good resistance to CO2 and H2O corrosion, good long-term stability, high ionic conductivity and low-temperature stability. The cerium oxide-based electrolyte material of the present invention is used with NiO anode material and LSF-BZCY cathode material to prepare a single cell, which has excellent properties such as long-term stability and high output power. The above excellent properties can make the electrolyte of the present invention have high application value in the fields of mobile power, transportation, fixed power stations, microgrids, drones, military industry, etc.
[0030] The above description is only an overview of the technical solution of the present invention. In order to more clearly understand the technical means of the present invention and implement it according to the contents of the specification, the preferred embodiments of the present invention are described in detail as follows. DETAILED DESCRIPTION
[0031] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the following is a detailed description of a solid oxide fuel cell electrolyte and its preparation method and application according to the present invention, its specific implementation, structure, characteristics and effects in combination with the preferred embodiment. In the following description, different "one embodiment" or "embodiment" does not necessarily refer to the same embodiment. In addition, specific features, structures or characteristics in one or more embodiments may be combined in any suitable form.
[0032] Unless otherwise specified, the materials, reagents, etc. involved below are all commercially available products well known to those skilled in the art; unless otherwise specified, the methods described are all methods known in the art. Unless otherwise defined, the technical terms or scientific terms used should have the usual meanings understood by ordinary technicians in the field to which the present invention belongs. If no specific experimental steps or conditions are specified below, the operations or conditions of the conventional experimental steps described in the literature in the field can be followed.
[0033] Some embodiments of the present invention provide a solid oxide fuel cell electrolyte having a chemical formula of Ce 0.8 Ca x Sn y Sb (0.2-x-y) O3, wherein x is 0.01-0.1, and y is 0.1-0.15. When x is less than 0.01 or greater than 0.1, and y is less than 0.1 or greater than 0.15, the electrolyte's ability to resist CO2 and H2O erosion, long-term stability, ionic conductivity, and low-temperature stability are reduced.
[0034] In some embodiments, optionally, the solid oxide fuel cell electrolyte may include, by mole percentage:
[0035] Cerium oxide 80 mol%;
[0036] 20 mol% of doping elements. The doping elements include calcium, tin, antimony and other elements to improve the ionic conductivity of the electrolyte, and the proportion of each doping element is adjustable.
[0037] In some embodiments, optionally, the solid oxide fuel cell electrolyte further comprises 5-10wt% of an additive, based on the total mass of the electrolyte. The additive is a compatibility enhancer. Further, the compatibility enhancer is calcium zirconate, which can improve the thermal stability and anti-pollution ability of the electrolyte.
[0038] After testing, the oxygen ion conductivity of the electrolyte for solid oxide fuel cells at 400°C is ≥0.1S / cm; after high-temperature cycle testing, the electrolyte maintains good structural stability at 800°C without obvious phase change or cracks; in an environment containing H2O and CO2, the electrolyte exhibits excellent anti-pollution properties, with an oxygen ion conductivity of ≥0.07S / cm.
[0039] In the above technical solution, Ce 4+ With a larger ionic radius (0.097nm), the more open structure is conducive to the migration of oxygen ions, so the cerium-based electrolyte exhibits higher conductivity. However, in the doped CeO2 (DCO) electrolyte, the Ce element exists in two valence states, +3 and +4. In a reducing atmosphere, Ce 4+ Easily reduced to Ce 3+ , resulting in increased electronic conductivity and manufacturing costs, ultimately reducing the open circuit voltage and output power of the battery, and also reducing the mechanical strength of the electrolyte layer and fuel utilization. In order to obtain a high concentration of carriers (i.e., oxygen vacancies), the present invention achieves charge compensation by co-doping divalent and / or trivalent rare earth / alkaline earth metal cations. Following the principle of maximizing oxygen ion mobility with minimal lattice distortion, calcium (Ca) is preferably added. 2+ ), tin (Sn 2+ ), antimony (Sb 3+ ) and other elements. 2+ (0.099nm), Sn 2+ (0.093nm), Sb 3+ (0.092nm) and Ce 4+ (0.097) is similar in radius, so the defect binding energy is low. The limit solid solubility of stannous oxide and antimony trioxide in cerium oxide is 40%, while the limit solid solubility of calcium oxide in cerium oxide is only 23%. At low doping levels, the increase in ionic conductivity of the electrolyte material is the result of an increase in oxygen vacancies, while at high doping levels, although the oxygen vacancies increase, the electrostatic attraction between the oxygen vacancies and the doped ions and the repulsive force between the oxygen vacancies are enhanced, making it difficult for the oxygen vacancies to migrate, resulting in a decrease in the conductivity of the oxygen ions, so the total doping amount of the present invention does not exceed 20%. On the other hand, the present invention limits the doping of calcium (Ca 2+ ), tin (Sn 2+ ), antimony (Sb 3+ ) and other elements, specifically Ce 0.8 Ca x Sn y Sb (0.2-x-y)O3 (CCSS, x is 0.01-0.1, y is 0.1-0.15). Co-doping can not only suppress electronic conductivity, but also improve the open circuit voltage of the battery. In the temperature range of 400-700°C, the oxygen ion conductivity of multi-doped cerium oxide-based electrolyte materials is significantly higher than that of undoped or single-doped cerium oxide electrolyte materials.
[0040] The present invention is based on the cerium oxide electrolyte material, doped with trivalent cation Sb 3+ , improve low temperature ionic conductivity; doping with Ca 2+ , improve ionic conductivity, sintering activity, and long-term stability; doping Sn 2+ , improve the long-term stability of the composite material, and the ability to resist CO2 and H2O atmosphere. The electrolyte for solid oxide fuel cells has good resistance to CO2 and H2O erosion, good long-term stability, high ionic conductivity and low-temperature stability. It can solve the problems of insufficient oxygen vacancies, decreased low-temperature ionic conductivity, weak resistance to CO2 and H2O, poor long-term stability in the working environment and low conductivity after improved stability in cerium-based electrolyte materials. The cerium oxide-based electrolyte material of the present invention is used to prepare a single cell with an anode material and a cathode material, which has excellent properties such as long-term stability and high output power. The above excellent properties can make the electrolyte material described in the invention have a high application value in the fields of mobile power supplies, transportation, fixed power stations, microgrids, drones, military industry, etc.
[0041] Some embodiments of the present invention also provide a method for preparing an electrolyte for a solid oxide fuel cell, comprising the following steps:
[0042] Step 1: mixing cerium oxide, doping elements and additives in proportion, and obtaining mixed powder by ball milling;
[0043] Step 2: sintering the mixed powder obtained in step 1 at 1100-1300° C. for 5-7 hours to obtain a crude electrolyte (forming a dense electrolyte ceramic);
[0044] Step 3: Annealing the crude electrolyte obtained in step 2 at 500-550° C. for 1-3 hours to improve its microstructure and ionic conductivity.
[0045] Some embodiments of the present invention also provide a method for preparing an electrolyte for a solid oxide fuel cell, comprising the following steps:
[0046] Step S1: mixing cerium oxide, doping elements and additives in proportion to obtain a mixed powder;
[0047] Step S2: Add 0.1-5wt% of adhesive and solvent to the mixed powder obtained in step S1, stir evenly to obtain a mixed slurry; shape the obtained mixed slurry into a sheet film with a thickness of less than 50μm, preferably, the thickness of the film is less than 20μm. More preferably, the thickness of the film is less than 15μm. More preferably, the thickness of the film is less than 10μm; use at least one of laser cutting and mechanical cutting to cut the sheet film into the required length and width specifications; the solvent is pure water or ethanol. The mixed slurry uses a vacuum degassing machine to remove internal gaseous inclusions. The mixed slurry is formed using at least one of a casting machine, screen printing, electrophoretic deposition, and spray pyrolysis method.
[0048] Step S3: Sinter the film obtained in step S2 at 1100-1300° C. for 4-6 hours to obtain the electrolyte for the solid oxide fuel cell (forming a dense electrolyte ceramic membrane strip).
[0049] Some embodiments of the present invention further provide a fuel cell, including an electrolyte, a NiO anode material, and a LSF-BZCY cathode material, wherein the electrolyte is the above-mentioned electrolyte for solid oxide fuel cells.
[0050] After testing, the fuel cell has a Ce 0.8 Ca x Sn y Sb (0.2-x-y) The oxygen ion conductivity of O3 (CCSS, x is 0.01-0.1, y is 0.1-0.15) is ≥0.1S / cm; after high temperature cycle test, the electrolyte maintains good structural stability at 800℃ without obvious phase change or cracks; in an environment containing H2O and CO2, the electrolyte shows excellent anti-pollution properties, and the oxygen ion conductivity is ≥0.07S / cm. 0.8 Ca x Sn y Sb (0.2-x-y) O3 (CCSS, x is 0.01-0.1, y is 0.1-0.15) and NiO anode material, LSF-BZCY cathode material to prepare a single cell, the fuel cell output power drop ratio in the test environment at 600 ℃ 10 hours <5%, the output power drop ratio after 100 hours of operation <10%; while the output power drop ratio of the single cell prepared by undoped Ca, Sn, Sb element materials after 10 hours of operation is ≥30%, and the output power drop ratio after 100 hours of operation is ≥70%. The maximum power density of the fuel cell at 400 ℃ is ≥200mW / cm 2 , preferably greater than 240mW / cm 2 , while the maximum power density of a single cell of an undoped ceria-based electrolyte material system is less than 150 mW / cm2 .
[0051] The present invention is further described below in conjunction with specific embodiments.
[0052] Example 1
[0053] This embodiment provides an electrolyte for a solid oxide fuel cell. The electrolyte for a solid oxide fuel cell is a cerium oxide-based electrolyte material, and its chemical formula is Ce 0.8 Ca 0.0 Sn 0.11 Sb 0.06 O3.
[0054] The cerium oxide-based electrolyte material Ce 0.8 Ca 0.03 Sn 0.11 Sb 0.06 O3 can be prepared by the following steps
[0055] Ce 0.8 Ca 0.03 Sn 0.11 Sb 0.06 Based on 1 mol of O3, the mass of calcium carbonate, stannous oxide, antimony trioxide and cerium oxide required are calculated according to the molar ratio of 0.8:0.03:0.11:0.06. 0.8 Ca 0.03 Sn 0.11 Sb 0.06 The mass of O3 is 100g as the reference, and 6.5g of calcium zirconate (BaZrO2) is added as a compatibility enhancer; calcium carbonate, stannous oxide, antimony trioxide, cerium oxide and calcium zirconate are mixed, and further uniformly mixed by ball milling (300rpm, 1 hour); the obtained mixed powder is sintered at 1250℃ for 6 hours to form a dense electrolyte ceramic; the obtained electrolyte ceramic is annealed at 530℃ for 2 hours to obtain the cerium oxide-based electrolyte material Ce 0.8 Ca 0.03 Sn 0.11 Sb 0.06 O3.
[0056] The cerium oxide-based electrolyte material Ce 0.8 Ca 0.03 Sn 0.11 Sb 0.06 O3 can also be prepared by the following steps:
[0057] Ce 0.8 Ca 0.03 Sn 0.11 Sb 0.06Based on 1 mol of O3, the masses of calcium carbonate, stannous oxide, antimony trioxide and cerium oxide required are calculated according to the molar ratio of 0.8:0.03:0.11:0.06. 0.8 Ca 0.03 Sn 0.11 Sb 0.06 The mass of O3 is 100g, and 6.5g of calcium zirconate (BaZrO2) is added as a compatibility enhancer; based on the molar percentage, calcium carbonate, stannous oxide, antimony trioxide, cerium oxide, and calcium zirconate are weighed and mixed in proportion. Based on the mass percentage of the above mixture, 0.4wt% PBV (polyvinyl butyral) and 20wt% anhydrous ethanol are additionally weighed and mixed to form a slurry with a solid content of 79wt%. After vacuum degassing (vacuum degree of -1Pa, 2h), an electrolyte membrane strip with a thickness of 15μm is formed by a tape casting machine. After cutting, the binder is removed at 450℃ for 3h and sintered at 1250℃ for 5h to form a dense electrolyte film, that is, the cerium oxide-based electrolyte material Ce is obtained. 0.8 Ca 0.03 Sn 0.11 Sb 0.06 O3.
[0058] After testing, at 400°C, the cerium oxide-based electrolyte material Ce 0.8 Ca 0.03 Sn 0.11 Sb 0.06 The oxygen ion conductivity of O3 is 0.132S / cm; after high temperature cycle testing, the electrolyte maintains good structural stability at 800°C without obvious phase change or cracks. In an environment containing H2O and CO2, the oxygen ion conductivity is 0.097S / cm.
[0059] The cerium oxide-based electrolyte material Ce 0.8 Ca 0.03 Sn 0.11 Sb 0.06 O3 and NiO anode materials, LSF-BZCY cathode materials to prepare a single cell, the maximum power density at 400 ° C is 267mW / cm 2 At 600°C, the output power decreases by 3.3% after 10 hours in the test environment, and by 7.9% after 100 hours of operation.
[0060] Example 2
[0061] The difference between this embodiment and embodiment 1 is that x in this embodiment is 0.01; the remaining steps and parameters are the same as those in embodiment 1.
[0062] After testing, at 400°C, the cerium oxide-based electrolyte material Ce 0.8 Ca 0.01 Sn 0.11 Sb 0.08 The oxygen ion conductivity of O3 is 0.124S / cm; after high temperature cycle testing, the electrolyte maintains good structural stability at 800°C without obvious phase change or cracks. In an environment containing H2O and CO2, the oxygen ion conductivity is 0.086S / cm.
[0063] The cerium oxide-based electrolyte material Ce 0.8 Ca 0.03 Sn 0.11 Sb 0.06 O3 and NiO anode materials, LSF-BZCY cathode materials to prepare a single cell, the maximum power density at 400 ℃ is 259mW / cm 2 At 600°C, the output power decreases by 3.9% after 10 hours in the test environment, and by 8.7% after 100 hours of operation.
[0064] Example 3
[0065] The difference between this embodiment and embodiment 1 is that x in this embodiment is 0.1; the remaining steps and parameters are the same as those in embodiment 1.
[0066] After testing, at 400°C, the cerium oxide-based electrolyte material Ce 0.8 Ca 0.1 Sn 0.1 The oxygen ion conductivity of Sb0O3 is 0.109S / cm; after high temperature cycle testing, the electrolyte maintains good structural stability at 800°C without obvious phase change or cracks. In an environment containing H2O and CO2, the oxygen ion conductivity is 0.074S / cm.
[0067] The cerium oxide-based electrolyte material Ce 0.8 Ca 0.1 Sn 0.1 The single cell was prepared by Sb0O3 and NiO anode materials and LSF-BZCY cathode materials. The maximum power density was 232mW / cm at 400℃. 2 At 600°C, the output power decreases by 4.9% after 10 hours in the test environment, and by 9.7% after 100 hours of operation.
[0068] Example 4
[0069] The difference between this embodiment and embodiment 1 is that y in this embodiment is 0.1; the remaining steps and parameters are the same as those in embodiment 1.
[0070] After testing, at 400°C, the cerium oxide-based electrolyte material Ce 0.8 Ca 0.03 Sn 0.1 Sb 0.07 The oxygen ion conductivity of O3 is 0.139S / cm; after high temperature cycle testing, the electrolyte maintains good structural stability at 800°C without obvious phase change or cracks. In an environment containing H2O and CO2, the oxygen ion conductivity is 0.099S / cm.
[0071] The cerium oxide-based electrolyte material Ce 0.8 Ca 0.03 Sn 0.11 Sb 0.06 O3 and NiO anode materials, LSF-BZCY cathode materials to prepare single cells, the maximum power density at 400 ℃ is 270mW / cm 2 At 600°C, the output power decreases by 3.0% after 10 hours in the test environment, and by 6.5% after 100 hours of operation.
[0072] Example 5
[0073] The difference between this embodiment and embodiment 1 is that y in this embodiment is 0.15; the remaining steps and parameters are the same as those in embodiment 1.
[0074] After testing, at 400°C, the cerium oxide-based electrolyte material Ce 0.8 Ca 0.03 Sn 0.15 Sb 0.02 The oxygen ion conductivity of O3 is 0.111S / cm; after high temperature cycle testing, the electrolyte maintains good structural stability at 800°C without obvious phase change or cracks. In an environment containing H2O and CO2, the oxygen ion conductivity is 0.082S / cm.
[0075] The cerium oxide-based electrolyte material Ce 0.8 Ca 0.03 Sn 0.15 Sb 0.02 O3 and NiO anode materials, LSF-BZCY cathode materials to prepare a single cell, the maximum power density at 400 ° C is 244mW / cm 2 At 600°C, the output power drops by 4.1% after 10 hours in the test environment, and by 8.4% after 100 hours of operation.
[0076] Comparative Example 1:
[0077] This comparative example provides an electrolyte for a solid oxide fuel cell, wherein the electrolyte for a solid oxide fuel cell is a single-doped cerium oxide electrolyte, and its chemical formula is Ce 0.9 G 0.1 O 1.95 .
[0078] The above single-doped cerium oxide electrolyte Ce 0.9 Gd0.1O 195 It can be prepared by the following steps:
[0079] Ce 0.9 G 0.1 O 195 The amount of substance is 1 mol as a benchmark, and the masses of the required raw materials cerium oxide and gadolinium oxide are calculated according to the molar ratio of 0.8:0.1; after mixing cerium oxide and gadolinium oxide, further uniformly mix them by ball milling (300 rpm, 1 hour); sintering the obtained mixed powder at 1250°C for 6 hours to form a dense electrolyte ceramic; annealing the obtained electrolyte ceramic at 530°C for 2 hours to obtain the cerium oxide-based electrolyte material Ce 0.8 Ca 0.03 Sn 0.11 Sb 0.06 O3.
[0080] The above single-doped cerium oxide electrolyte Ce 0.9 G 0.1 O 1.95 It can also be prepared by the following steps:
[0081] Ce 0.9 G 0.1 O 1.95 The amount of substance is 1 mol as the benchmark, and the mass of the required raw materials cerium oxide and gadolinium oxide is calculated according to the mass ratio of 0.9:0.1; based on the mass of cerium oxide and gadolinium oxide, 0.4wt% of PBV (polyvinyl butyral) and 20wt% of anhydrous ethanol are additionally weighed to form a slurry, and the solid content of the slurry is 78%. After vacuum degassing (vacuum degree is -1Pa, 2h), an electrolyte membrane strip with a thickness of 15um is formed by a casting machine. After cutting, the binder is removed at 450℃ for 3h and sintered at 1250℃ for 5h to form a dense electrolyte film, that is, the single-doped cerium oxide electrolyte is obtained.
[0082] After testing, at 400°C, the single-doped cerium oxide electrolyte Ce 0.9 G 0.1 O 1.95The oxygen ion conductivity is 0.02S / cm; after high temperature cycle testing, the electrolyte has obvious cracks at 800°C. In an environment containing H2O and CO2, the oxygen ion conductivity is 0.008S / cm.
[0083] The single-doped cerium oxide electrolyte Ce of this comparative example 0.9 G 0.1 O 195 The single cell was prepared with NiO anode material and LSF-BZCY cathode material, and the maximum power density was 122mW / cm at 400℃ 2 At 600°C, the output power decreases by 45.1% after 10 hours in the test environment, and by 79.6% after 100 hours of operation.
[0084] In summary, the multi-doped cerium oxide-based electrolyte material of the present invention has good resistance to CO2 and H2O corrosion, good long-term stability, high ionic conductivity and low-temperature stability. The cerium oxide-based electrolyte material of the present invention is combined with NiO anode material and LSF-BZCY cathode material to prepare a single cell, which has excellent properties such as long-term stability and high output power. The above excellent properties can make the electrolyte described in the present invention have high application value in the fields of mobile power, transportation, fixed power stations, microgrids, drones, military industry, etc.
[0085] The above embodiments are only used to explain the content of the present invention, and are not intended to limit the present invention. Simple technical variations within the technical concept of the present invention should be considered to be covered by the content disclosed by the present invention and belong to the protection scope of the present invention.
[0086] In the specification of the present invention, a lot of specific details are described. However, it is understood that embodiments of the present invention can be practiced without these specific details. In some embodiments, well-known methods, structures and techniques are not shown in detail so as not to obscure the understanding of this specification.
[0087] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.
[0088] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.
[0089] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Any simple modification, equivalent change and modification made to the above embodiment according to the technical essence of the present invention still falls within the scope of the technical solution of the present invention.
Claims
1. An electrolyte for a solid oxide fuel cell, characterized in that: Its chemical formula is Ce 0.8 Ca x Sn y Sb (0.2-x-y) O3, wherein x is 0.01-0.1 and y is 0.1-0.
15.
2. The solid oxide fuel cell electrolyte according to claim 1, wherein The electrolyte for solid oxide fuel cells comprises, by mole percentage: Cerium oxide 80 mol%; Doping element 20 mol%.
3. The solid oxide fuel cell electrolyte according to claim 1, wherein The doping elements include calcium, tin and antimony.
4. The solid oxide fuel cell electrolyte according to claim 1, wherein The electrolyte for solid oxide fuel cells further comprises 5-10 wt % of an additive; the additive is a compatibility enhancer.
5. The solid oxide fuel cell electrolyte according to claim 4, characterized in that The compatibility enhancer is calcium zirconate.
6. The solid oxide fuel cell electrolyte according to claim 1, wherein The oxygen ion conductivity of the electrolyte for solid oxide fuel cells at 400°C is ≥0.1S / cm; after high-temperature cycle testing, the electrolyte for solid oxide fuel cells maintains good structural stability at 800°C without obvious phase change or cracks; in an environment containing H2O and CO2, the electrolyte for solid oxide fuel cells exhibits excellent anti-pollution properties, with an oxygen ion conductivity of ≥0.07S / cm.
7. A method for preparing an electrolyte for a solid oxide fuel cell, characterized in that: The following steps are involved: Step 1: mixing cerium oxide, doping elements and additives in proportion to obtain mixed powder; Step 2: sintering the mixed powder obtained in step 1 at 1100-1300° C. for 5-7 hours to obtain a crude electrolyte; Step 3: annealing the crude electrolyte obtained in step 2 at 500-550° C. for 1-3 hours to obtain the electrolyte for solid oxide fuel cells.
8. A method for preparing an electrolyte for a solid oxide fuel cell, characterized in that: The following steps are involved: Step S1: mixing cerium oxide, doping elements and additives in proportion to obtain a mixed powder; Step S2: adding 0.1-5wt% of an adhesive and a solvent to the mixed powder obtained in step S1, and stirring evenly to obtain a mixed slurry; forming the obtained mixed slurry into a sheet film with a thickness of less than 50 μm, and cutting the sheet film; Step S3: sintering the film obtained in step S2 at 1100-1300° C. for 4-6 hours to obtain the electrolyte for the solid oxide fuel cell.
9. The method for preparing a solid oxide fuel cell electrolyte according to claim 8, characterized in that: In step S2, the solvent is pure water or anhydrous ethanol.
10. A fuel cell, characterized in that: The invention comprises an electrolyte, wherein the electrolyte is the electrolyte for a solid oxide fuel cell according to any one of claims 1 to 6.